О дохлой кошке и живых котятах - Бутовская Марина (Другой, другие, о других, 2008)
Экземпляры: ф.2 (20140619) / Инвентарный номер: 48687 / Цена: 150.00 / Авт.знак: Б 93 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6